Assessing the Impact of Nurse-Delivered Personalized Nutrition Counseling on Pregnancy Outcomes in Gestational Diabetes Mellitus: A Qualitative Study in Al Majmaah City - Abdulmohsen Abdullah Eid Alalwani; Manal Owaebed Allogmani; Reem Salem Al Saedi; Ibrahim Saud Aloufi; Abdulrahman Nasser Abdullah Alshahrani; Nader Saud Aloufi; Majed Ied Aljohani; Abdullah Nasser Abdullah Alshahrani; Wael Muneer S Alraddadi; Abdullah Mohammed Moslem Aljohani; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Gestational diabetes mellitus (GDM) is a common complication of pregnancy that can lead to adverse outcomes for both mother and child. Personalized nutrition counseling delivered by nurses has shown promise in managing GDM and improving pregnancy outcomes. This qualitative study aimed to assess the impact of nurse-delivered personalized nutrition counseling on pregnancy outcomes in women with GDM in Al Majmaah City, Saudi Arabia. Semi-structured interviews were conducted with 25 pregnant women diagnosed with GDM who received personalized nutrition counseling from trained nurses at a primary healthcare center. Thematic analysis was used to identify key themes related to the women’s experiences and perceived impact of the intervention. Four main themes emerged: 1) increased knowledge and awareness of GDM and healthy eating, 2) improved dietary habits and glycemic control, 3) enhanced self-efficacy and motivation, and 4) positive pregnancy outcomes. Participants reported that the personalized approach, ongoing support, and practical guidance provided by nurses helped them better understand and manage their condition, leading to improved blood sugar levels, healthy weight gain, and reduced complications. These findings suggest that nurse-delivered personalized nutrition counseling is a promising intervention for improving pregnancy outcomes in women with GDM in Saudi Arabia. Larger-scale studies are needed to further evaluate its effectiveness and feasibility in different settings. Integrating this approach into routine antenatal care could potentially improve maternal and child health outcomes related to GDM.